Pemberdayaan Perempuan Dalam Peningkatan Pendidikan Berkualitas: Menyatukan Visi - Muhalida Zia Ibhar; Jesika Puteri; Wahyu Andika Putra (UNIB Press, 2024)
Empowering women for quality education: uniting the vision aimed at increasing women's participation in supporting quality education. This research identifies the various challenges faced by women in gaining access to quality education and empowers them through collaborative efforts to unite their vision. This service method involves a series of activities such as workshops, training and group discussions to empower women in an educational environment. In addition, a participatory approach is also used to involve communities in identifying sustainable solutions. The results of this activity show increased public awareness of the importance of quality education for women and effective collaborative strategies in achieving this goal. Through women's empowerment and unified vision, it is hoped that an inclusive and sustainable educational environment can be created for all groups.